ASSOCIATION BETWEEN THROMBOLYSIS IN MYOCARDIAL INFARCTION (TIMI) RISK SCORE AND CORONARY VESSEL INVOLVEMENT IN PATIENTS WITH NON-ST-ELEVATION MYOCARDIAL INFARCTION AND UNSTABLE ANGINA – A RETROSPECTIVE OBSERVATIONAL RECORD-BASED STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Most acute coronary presentations are caused by non-ST-elevation acute coronary syndromes (NSTE-ACS), which include non-ST-elevation myocardial infarction (NSTEMI) and unstable angina (UA). The severity of these conditions varies significantly. Although the Thrombolysis in Myocardial Infarction (TIMI) risk score is a validated bedside tool for risk stratification, its association with the angiographic severity of coronary artery disease (CAD) has not been sufficiently investigated in the Indian population. The purpose of this study was to ascertain whether the degree of coronary vascular involvement in individuals with NSTEMI and UA was correlated with the TIMI risk score. Methods: This retrospective observational record-based study was conducted among 98 patients diagnosed with NSTEMI or UA who underwent coronary angiography at a tertiary care center in Puducherry, India, between January 2024 and June 2025. Patient data were extracted from medical records using ICD-10 codes and validated proformas. TIMI scores were calculated using seven clinical and laboratory parameters and categorized as